Make ink : a forager's guide to natural inkmaking - Logan, Jason (Artist) (Abrams, 2018)
The Toronto Ink Company was founded in 2014 by designer and artist Jason Logan as a citizen science experiment to make eco-friendly, urban ink from street-harvested pigments. In Make Ink, Logan delves into the history of inkmaking and the science of distilling pigment from the natural world. Readers will learn how to forage for materials such as soot, rust, cigarette butts, peach pits, and black walnut, then how to mix, test, and transform these ingredients into rich, vibrant inks that are sensitive to both place and environment. Organized by color, and featuring lovely minimalist photography throughout, Make Ink combines science, art, and craft to instill the basics of ink making and demonstrate the beauty and necessity of engaging with one of mankind<U+2019>s oldest tools of communication.